Life cycle and host specificity of Amblyomma triste (Acari : Ixodidae) under laboratory conditions - Labruna, M. B.; Fugisaki, EYM; Pinter, A.; Duarte, JMB; Szabo, MJP (Kluwer Academic Publ, 2003)
We report biological data of two generations of Amblyomma triste in laboratory and compared the suitability of different host species. Infestations by larval and nymphal stages were performed on guinea pigs (Cavia porcellus), chickens (Gallus gallus), rats (Rattus norvegicus), rabbits (Oryctolagus cuniculus), wild mice (Calomys callosus), dogs (Canis familiaris) and capybaras (Hydrochaeris hydrochaeris). Infestations by adult ticks were performed on dogs, capybaras and rabbits. Tick developmental periods were observed in an incubator at 27degreesC and RH 90%. Guinea pigs were the most suitable hosts for larvae and nymphs, followed by chickens. The remaining host species were less suitable for immature ticks as fewer engorged ticks were recovered from them. Mean larval feeding periods varied from 3.8 to 4.7 d between different host species. Mean larval premolt periods ranged from 8.9 to 10.4 d. Nymphal mean feeding periods varied from 4.2 to 6.2 d for ticks fed on different host species. Premolt period of male nymphs (mean: 15.4 d) was significantly longer than that of female nymphs (14.7 d). Female nymphs were significantly heavier than male nymphs. The overall sex ratio of the adult ticks emerged from nymphs was 0.9:1 (M:F). Capybaras were the most suitable host for the tick adult stage as significantly more engorged females were recovered from them and these females were significantly heavier than those recovered from dogs or rabbits. The life cycle of A. triste in laboratory could be completed in an average period of 155 d. The potential role of guinea pigs, birds and capybaras, as hosts for A. triste in nature, is discussed.
Keywords: Amblyomma triste; host preference; Ixodidae; life cycle